A Purchase Decision Behavior Model by Generation Z: The Mediating Role of Consumer Motivation - Sudrajat, Ajat; Kusnanto, Danang; Megawati, Liya; Millasyfa, Nadya; Mardiah, Dinda; Oktavianita, Ayu (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Given Generation Z’s significant dependence on e-commerce platforms, it is crucial to understand how they shop in the digital economy. However, limited studies have examined how affiliate marketing and advertising influence actual purchase decisions, particularly when mediated by consumer motivation. Method: A quantitative explanatory design was employed using a survey of 200 Generation Z respondents aged 18 to 26 who actively make online purchases. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. A bootstrapping approach was applied to test the mediation effect. Results: The findings indicate that advertising has a significant influence on consumers’ purchase decisions (β = 0.578, p < 0.05), whereas affiliate marketing does not. Both affiliate marketing and advertising positively influence consumer motivation; however, motivation does not significantly affect purchase decisions Conclusion: These findings advance motivation theory by highlighting the greater influence of external digital stimuli over intrinsic drivers in shaping Generation Z’s purchasing behavior. Practically, the study suggests that Indonesian e-commerce platforms, such as Shopee and Tokopedia, should prioritize interactive and storytelling-based advertising combined with urgency-driven strategies (e.g., flash sales and exclusive promotions) to enhance purchase effectiveness